Juvenile localized scleroderma: Clinical and epidemiological features in 750 children. An international study - Zulian, F.; Athreya, B. H.; Laxer, R.; Nelson, A. M.; Feitosa de Oliveira, S. K.; Punaro, M. G.; Cuttica, R.; Higgins, G. C.; Van Suijlekom-Smit, L. W A; Moore, T. L.; Lindsley, C.; Garcia-Consuegra, J.; et al. (Oxford University Press (OUP), 2006)
Objective. Juvenile localized scleroderma (JLS) includes a number of conditions often grouped together. With the long-term goal of developing uniform classification criteria, we studied the epidemiological, clinical and immunological features of children with JLS followed by paediatric rheumatology and dermatology centres. Methods. A large, multicentre, multinational study was conducted by collecting information on the demographics, family history, triggering environmental factors, clinical and laboratory features, and treatment of patients with JLS. Results. Seven hundred and fifty patients with JLS from 70 centres were enrolled into the study. The disease duration at diagnosis was 18 months. Linear scleroderma (LS) was the most frequent subtype (65%), followed by plaque morphea (PM) (26%), generalized morphea (GM) (7%) and deep morphea (DM) (2%). As many as 15% of patients had a mixed subtype. Ninety-one patients (12%) had a positive family history for rheumatic or autoimmune diseases; 100 (13.3%) reported environmental events as possible trigger. ANA was positive in 42.3% of the patients, with a higher prevalence in the LS-DM subtype than in the PM-GM subtype. Scl70 was detected in the sera of 3% of the patients, anticentromere antibody in 2%, anti-double-stranded DNA in 4%, anti-cardiolipin antibody in 13% and rheumatoid factor in 16%. Methotrexate was the drug most frequently used, especially during the last 5 yr. Conclusion. This study represents the largest collection of patients with JLS ever reported. The insidious onset of the disease, the delay in diagnosis, the recognition of mixed subtype and the better definition of the other subtypes should influence our efforts in educating trainees and practitioners and help in developing a comprehensive classification system for this syndrome. © 2006 Oxford University Press.
Keywords: Morphea; Parry-Romberg syndrome; Progressive hemifacial atrophy; Scleroderma; Scleroderma en coup de sabre; agents acting on the eye; anticonvulsive agent; antinuclear antibody; azathioprine; cardiolipin antibody; centromere antibody; cyclophosphamide; cyclosporin A; emollient agent; histamine H2 receptor antagonist; immunosuppressive agent; methotrexate; methoxsalen; mycophenolic acid 2 morpholinoethyl ester; nonsteroid antiinflammatory agent; penicillamine; prokinetic agent; rheumatoid factor; scl 70 antibody; steroid; vitamin D; adolescent; autoimmune disease; child; clinical feature; demography; disease classification; disease duration; drug use; environmental factor; epidemiological data; family history; female; follow up; human; infant; laboratory test; linear scleroderma; localized scleroderma; major clinical study; male; morphea; patient care; priority journal; PUVA; rheumatic disease; Adolescent; Age of Onset; Autoantibodies; Autoimmune Diseases; Child; Child, Preschool; Environment; Female; Genetic Predisposition to Disease; Humans; Immunosuppressive Agents; Infant; Infant, Newborn; International Cooperation; Male; Methotrexate; Rheumatic Diseases; Risk Factors; Scleroderma, Localized